Karakterisasi Senyawa Pestisida pada Nanopartikel Ekstrak Bawang Putih (Allium Sativum L.) dan Uji Mortalitas Terhadap Ulat Grayak (Spodoptera Litura F.) di Laboratorium - Wahyu Ramadhani Putra Josua; Wiwin Windriyanti; Ramadhani Mahendra Kusuma (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to characterize the pesticide compounds in garlic (Allium sativum L.) extract nanoparticles and test their mortality effectiveness against armyworms (Spodoptera litura F.) in the laboratory. Nanoparticle synthesis was carried out using the ionic gelation method with chitosan-TPP, which was subsequently characterized using PSA, SEM, FT-IR, and GC-MS. The characterization results showed a particle size of 930.52 nm with a homogeneous distribution (PDI 0.147). GC-MS analysis successfully identified the main bioactive organosulfur compounds, namely diallyl disulfide (20.72%), diallyl trisulfide (14.16%), and diallyl tetrasulfide (5.79%). Bioactivity testing using the sandwich method at five concentration variations (0-1%) showed the highest mortality reaching 70% at a 1% concentration. Probit analysis yielded values of LC₅₀ 1.116% and LC₉₀ 1.720%, as well as LT₅₀ 5.117 days and LT₉₀ 9.893 days. Statistical test results indicated a significant difference (p<0.05) between all treatments and the control group. Thus, it can be concluded that the garlic extract nanoparticle formulation has the potential to be an effective nano-bioinsecticide, with a mode of action that is dose-dependent and time-dependent in controlling S. litura larvae.